Investigation of low reynolds number airfoils for fixed-pitch straight-bladed VAWT - Islam, Mazharul; Amin, Mohammad Ruhul; Carriveau, Rupp; Fartaj, Amir (2009)
Selection of appropriate airfoil is very important for improved aerodynamic performance of a smaller-capacity fixed-pitch straight-bladed vertical axis wind turbine (SB-VAWT). Recently, Islam et. al1 have identified the desirable features of an ideal airfoil for smaller capacity SB-VAWT to improve its starting characteristics and overall performance. They have shortlisted several aerodynamic characteristics of the desirable airfoil. Based on these desirable aerodynamic characteristics, an attempt has been made in this paper to investigate the experimental results of different types of airfoils which meet the ideal characteristics of the desired airfoil identified by Islam et. al1 . After performing a screening process, seven prospective candidate low RN airfoils are selected. In this study,only the low RN experimental datasets are sought which are proved to be difficult to find since most public domain datasets are for high RN. It has been found that most of the candidate asymmetric airfoils are performing better than conventional NACA 0015 airfoil which has been extensively used for SB-VAWTs, especially for 0°≤α≤90°.